Solid-waste-based mine filling material as well as preparation method and use method thereof

By using solid waste-based mine filler in mine filler, combined with tailings, slag, modified fly ash and other components, the problem of water dissipation when the filling depth increases is solved, and the effect of adjustable density, improved freeze-thaw resistance and reduced cement consumption is achieved.

CN119638352APending Publication Date: 2025-03-18FOSHAN TRANSPORTATION SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633150.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When the filling depth of existing mines increases, the water leaks out and causes accidents such as collapse. The cement consumption is high and the cost is high, and the cement is a high pollution and high carbon emission product.

Method used

Solid waste-based mine filling materials are used, including tailings, slag, modified fly ash, phosphogypsum, soda ash, cement and foaming agent. By adjusting the formula and preparation method, fillers with adjustable density and are not prone to water leakage are prepared.

Benefits of technology

The density of the filler is adjustable, the water discharge rate is reduced, the anti-dry shrinkage and freeze-thaw properties of the filler are improved, the consumption of cement is reduced, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a solid-waste-based mine filling material as well as a preparation method and a use method thereof, and relates to the field of mine filling. The solid waste-based mine filling material comprises the following components in percentage by weight: 20-50% of tailings, 10-30% of slag, 10-30% of modified fly ash, 5-15% of phosphogypsum, 5-10% of sodium carbonate, 5-10% of cement and 1-10% of a foaming agent. Wherein a copolymer of PVA, polyacrylate or vinyl acetate and acrylate is formed on the surface of the modified fly ash. By implementing the method disclosed by the invention, bleeding of the solid-waste-based mine filling material can be greatly reduced, free adjustment of the density of the solid-waste-based mine filling material can be realized, and the consumption of cement and other components is reduced. Meanwhile, the dry shrinkage resistance and the freezing and thawing resistance of a filling body formed by the solid waste-based mine filling material are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of mine filling, and in particular to a solid waste-based mine filling material and a preparation method and a use method thereof. Background Art

[0002] Backfill mining refers to a mining method that uses backfill materials to fill the goaf during ore dropping, transportation and other operations. The purpose of backfilling is to support the rocks on both sides of the goaf and to create a foothold for the continued stratified mining above. Every year, a large number of goafs need to be filled in my country. The current conventional practice is to use cement as a cementitious material and mix it with tailings in a certain ratio to form a slurry to complete the filling. However, there are a series of problems: the density difference between slurry and water is large, which leads to water seepage and degassing when the filling depth increases, causing accidents such as collapse; in addition, the amount of tailings is usually not enough to fill the goaf, and a large amount of sand and gravel and other materials need to be purchased from outside, which is costly; in addition, cement is a high-pollution and high-carbon emission product, and cement should be used less or not in engineering. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a solid waste-based mine filling material with adjustable density, low water seepage, high safety factor and low cement consumption.

[0004] Another technical problem to be solved by the present invention is to provide a method for preparing solid waste-based mine filling materials.

[0005] Another technical problem to be solved by the present invention is to provide a method for using solid waste-based mine filling materials.

[0006] In order to solve the above technical problems, the present invention provides a solid waste-based mine filling material, which includes the following components in weight percentage:

[0007] Tailings 20-50%, slag 10-30%, modified fly ash 10-30%, phosphogypsum 5-15%, soda ash 5-10%, cement 5-10%, foaming agent 1-10%;

[0008] Wherein, the surface of the modified fly ash forms PVA, polyacrylate or a copolymer of vinyl acetate and acrylate.

[0009] As an improvement of the above technical solution, the modified fly ash is made from the following raw materials in parts by weight:

[0010] 80-100 parts of fly ash, 0.5-5 parts of alkali, 5-15 parts of PVA, and 3-12 parts of cellulose.

[0011] As an improvement of the above technical solution, the fly ash is Class F fly ash;

[0012] The base is selected from one or more of sodium hydroxide, potassium hydroxide and triethanolamine;

[0013] The polymerization degree of the PVA is 800-1200.

[0014] As an improvement of the above technical solution, the preparation method of the modified fly ash is:

[0015] The fly ash is mixed with alkali solution, reacted at 50-90°C for 0.1-0.5h, and the first intermediate product is obtained after solid-liquid separation and drying; wherein the alkali concentration in the alkali solution is 5-50g / L, and the ratio of the alkali solution to the fly ash is 100mL: (80-100)g;

[0016] The first intermediate product is mixed with PVA, cellulose and water to prepare a slurry with a solid content of 5 to 15 wt%, reacted at 80 to 120° C. for 10 to 40 minutes, and then dried at 60 to 80° C. to obtain modified fly ash.

[0017] As an improvement of the above technical solution, the steps of mixing fly ash with alkali solution, reacting at 50-90° C. for 0.1-0.5 h, and obtaining the first intermediate product after solid-liquid separation and drying include:

[0018] Sorting the fly ash to remove the floating beads and carbon particles in the fly ash to obtain the second intermediate product;

[0019] The second intermediate product is treated with an alkali solution having a concentration of 10 to 40 g / L for 0.2 to 0.5 h to obtain an intermediate product.

[0020] As an improvement of the above technical solution, the step of sorting the fly ash, removing the floating beads and carbon particles in the fly ash, and obtaining the second intermediate product includes:

[0021] Mixing fly ash with water to obtain a first slurry with a concentration of 20 to 40 wt%, and removing floating beads on the surface after standing;

[0022] The first ore pulp is floated using diesel as a collector and octanol as a foaming agent, and the first ore pulp after flotation is filtered and dried to obtain a second intermediate product;

[0023] The weight ratio of the diesel to the fly ash is (0.3-1.5):1000, the weight ratio of the 2-octanol to the fly ash is (0.4-1.5):1000, the flotation time is 3-5 minutes, and the aeration volume is 0.1-0.5 m 3 / (m 2 ·min).

[0024] As an improvement of the above technical solution, the foaming agent is sodium lauryl sulfate and / or sodium fatty alcohol polyoxyethylene ether sulfate;

[0025] The slag is S95 grade slag powder or S105 grade slag powder;

[0026] The cement is PO42.5 grade cement or PO52.5 grade cement;

[0027] The content of calcium sulfate dihydrate in the phosphogypsum is ≥75wt%.

[0028] As an improvement of the above technical solution, the average particle size of the tailings is 0.5-5 mm, and its particle size meets the following relationship:

[0029] D20*D20 / D80*D20=1.2~2;

[0030] D80 / D20=6-10;

[0031] Wherein, D20 is the aperture of the sieve corresponding to 20 wt% of the sieved weight, and D80 is the aperture of the sieve corresponding to 80 wt% of the sieved weight.

[0032] Correspondingly, the present invention also discloses a method for preparing a solid waste-based mine filling material, which is used to prepare the above-mentioned solid waste-based mine filling material, and comprises:

[0033] Prepare modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement and water to prepare a slurry with a water content of 30-40wt%;

[0034] The foaming agent is added with water to foam to obtain foam, and the foam is mixed with the slurry to obtain the foam.

[0035] Correspondingly, the present invention also discloses a method for preparing a solid waste-based mine filling material, which is used to use the above-mentioned solid waste-based mine filling material, and comprises:

[0036] Prepare solid waste-based mine filling materials, pump them into the goaf for filling and solidification.

[0037] The implementation of the present invention has the following beneficial effects:

[0038] The solid waste-based mine filling material of the present invention comprises the following components in percentage by weight: 20-50% of tailings, 10-30% of slag, 10-30% of modified fly ash, 5-15% of phosphogypsum, 5-10% of soda ash, 5-10% of cement, and 1-10% of foaming agent. Based on the above formula, on the one hand, a foaming agent is introduced into the solid waste-based mine filling material, and by adjusting its dosage, the density of the solid waste-based mine filling material can be made to be 800-1000kg / m 3Adjustable, so that the density of solid waste-based mine filling material is close to the density of water, greatly reducing water seepage. Second, by freely adjusting the density of solid waste-based mine filling material, the amount of filling material can be reduced and material consumption can be reduced. Third, by introducing various solid wastes, the consumption of cement is greatly reduced and the preparation cost is reduced. Fourth, by introducing soda ash, it not only plays the role of alkaline excitation and improves the mechanical properties, but also partially neutralizes the acidic components of phosphogypsum to avoid affecting the working performance of solid waste-based mine filling material. Fifth, PVA / polyacrylate / vinyl acetate-acrylate copolymer is formed on the surface of modified fly ash, which has good film-forming and water-retaining properties, can play a role in stabilizing foam, increase the thickness of the foam film, and make the solid waste-based mine filling material have good stability. Moreover, modified fly ash can also improve the anti-shrinkage and anti-freeze-thaw properties of the filling body formed by the solid waste-based mine filling material. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described below in conjunction with specific embodiments.

[0040] The present invention provides a solid waste-based mine filling material, which includes the following components in weight percentage:

[0041] Tailings 20-50%, slag 10-30%, modified fly ash 10-30%, phosphogypsum 5-15%, soda ash 5-10%, cement 5-10%, foaming agent 1-10%. Based on the above formula, a foaming agent is introduced into the solid waste-based mine filling material, and by adjusting its dosage, the density of the solid waste-based mine filling material can be made between 800 and 1000 kg / m 3 Adjustable, so that the density of solid waste-based mine filling material is close to the density of water, greatly reducing water seepage. Second, by freely adjusting the density of solid waste-based mine filling material, the amount of filling material can be reduced and material consumption can be reduced. Third, by introducing various solid wastes, the consumption of cement is greatly reduced and the preparation cost is reduced. Fourth, the introduction of soda ash not only plays the role of alkaline excitation and improves the mechanical properties, but also partially neutralizes the acidic components of phosphogypsum to avoid affecting the working performance of solid waste-based mine filling material. Fifth, PVA (polyvinyl alcohol) / polyacrylate / vinyl acetate-acrylate copolymer is formed on the surface of modified fly ash, which has good film-forming and water-retaining properties, can play a role in stabilizing foam, increase the thickness of the foam film, and make the solid waste-based mine filling material have good stability. Moreover, modified fly ash can also improve the anti-shrinkage and anti-freeze-thaw properties of the filling body formed by the solid waste-based mine filling material.

[0042] Specifically, fly ash can be directly mixed with monomers (vinyl acetate, alkyl acrylic acid, acrylic acid, vinyl acetate, etc.), and then a crosslinking agent and an initiator are added to react, and modified fly ash can be obtained after the reaction, but it is not limited thereto.

[0043] Preferably, in one embodiment, the modified fly ash is made from the following raw materials in parts by weight: 80-100 parts of fly ash, 0.5-5 parts of alkali, 5-15 parts of PVA, and 3-12 parts of cellulose.

[0044] The fly ash is Class F fly ash, which has strong reactivity and can improve the mechanical properties of solid waste-based mine filling materials. Exemplarily, the amount of fly ash is 84 parts, 88 parts, 92 parts, 96 parts or 98 parts, but is not limited thereto.

[0045] Wherein, the alkali is sodium hydroxide, potassium hydroxide or triethanolamine, but is not limited thereto. Preferably, the alkali is sodium hydroxide. The amount of the alkali used is 0.5 to 5 parts. If the amount is too much, water glass will be formed, which will thicken the solid waste-based mine filling material and reduce workability. Exemplarily, the amount of the alkali used is 0.8 parts, 1.2 parts, 1.6 parts, 2 parts, 2.4 parts, 2.8 parts, 3.2 parts, 3.6 parts, 4 parts, 4.4 parts, 4.8 parts, but is not limited thereto.

[0046] Wherein, the degree of polymerization of PVA is 800-1200, exemplarily 850, 900, 950, 1000, 1050, 1100 or 1150, but not limited thereto. Exemplarily, the amount of PVA used is 6 parts, 8 parts, 10 parts, 12 parts or 14 parts, but not limited thereto.

[0047] The average particle size of the cellulose is 30 to 50 μm. For example, the amount of cellulose is 4 parts, 6 parts, 8 parts or 10 parts, but is not limited thereto.

[0048] Based on the above formula, PVA can be formed on the surface of fly ash particles through hydrogen bonding, thereby improving the film-forming property and water retention of fly ash.

[0049] Preferably, in one embodiment, the method for preparing modified fly ash comprises the following steps:

[0050] S1: Mix fly ash and alkali solution, react at 50-90°C for 0.1-0.5h, separate solid and liquid, and dry to obtain a first intermediate product;

[0051] The alkali concentration in the alkali solution is 5-50 g / L, and the ratio of the alkali solution to the fly ash is 100 mL: (80-100) g. The glass part included on the surface of the fly ash microbeads is removed by alkali treatment, and at the same time, some hydroxyl groups are attached to the surface of the fly ash particles, which facilitates the subsequent attachment of cellulose and PVA to the surface of the fly ash particles.

[0052] S2: Mix the first intermediate product with PVA, cellulose and water to prepare a slurry with a solid content of 5 to 15 wt%, react at 80 to 120° C. for 10 to 40 minutes, and then dry at 60 to 80° C. to obtain modified fly ash.

[0053] More preferably, in one embodiment, step S1 comprises:

[0054] S11: sorting the fly ash to remove floating beads and carbon particles in the fly ash to obtain a second intermediate product;

[0055] S12: treating the second intermediate product with an alkali solution having a concentration of 10 to 40 g / L for 0.2 to 0.5 h to obtain an intermediate product.

[0056] It should be noted that fly ash is a solid waste collected in the flue gas after coal combustion. Its mineral phase composition is complex, including unburned carbon particles, high-temperature generated glass (a mixture of three or more of silicon, aluminum, calcium, magnesium, sodium, potassium, iron and titanium), and some crystalline phases (such as mullite, corundum, calcium sulfate, iron oxide, titanium oxide). In the process of coal combustion, the high temperature generated by the combustion causes some minerals in the coal to melt and react to form glass, which cools rapidly after being discharged from the flue. The glass generated at high temperature will shrink when the temperature drops suddenly to form some hollow microspheres (commonly known as floating beads); the glass will also wrap some crystalline phases to obtain solid or semi-solid microspheres; in addition, some residual carbon particles will adhere to the surface of the microspheres. When traditional mine filling materials use fly ash, hollow floating beads or fly ash as a whole are generally used. This is because the hollow floating beads are mainly highly active glass, which can quickly combine with other components (such as cement, slag, etc.) to form calcium silicate hydrate (CSH), thereby improving the curing strength. However, the inventors found that, firstly, since the floating beads are very light and have poor compatibility with other solid waste materials, the solid waste-based mine filling materials using the floating beads have poor uniformity and are prone to water seepage; secondly, the carbon particles on the surface of the fly ash particles make it difficult for PVA, polyacrylate, etc. to evenly adhere to the surface of the fly ash particles. To this end, the present invention first removes the floating beads and carbon particles in the fly ash by sorting, and then removes the glassy part wrapped on the surface of the fly ash particles by a weak base, forming hydroxyl groups on its surface, which allows the subsequent PVA and cellulose to better adhere to the surface of the fly ash particles.

[0057] Specifically, in step S11, the carbon particles in the fly ash can be separated by flotation, cyclone dust collector air separation, etc., but it is not limited thereto. Preferably, in one embodiment, step S11 includes the following steps:

[0058] S111: mixing fly ash with water to obtain a first slurry with a concentration of 20 to 40 wt%, and removing floating beads on the surface after standing;

[0059] S112: using diesel as a collector and octanol as a frother, flotating the first slurry, filtering and drying the first slurry after flotation to obtain a second intermediate product;

[0060] The weight ratio of diesel to fly ash is (0.3-1.5):1000, the weight ratio of octanol to fly ash is (0.4-1.5):1000, the flotation time is 3-5 minutes, and the aeration volume is 0.1-0.5m 3 / (m 2 ·min).

[0061] Specifically, in the solid waste-based mine filling material, the amount of modified fly ash used is 10-30%, exemplified by 14%, 18%, 22% or 26%, but not limited thereto.

[0062] Among them, slag is a powder material obtained by grinding granulated blast furnace slag to a specified fineness. It has high potential activity and can undergo hydration reaction under alkaline excitation conditions to improve mechanical properties. Specifically, the slag can be S95 grade or S105 grade, but not limited to this. Exemplarily, the amount of slag is 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26% or 28%, but not limited to this.

[0063] Among them, phosphogypsum is a solid waste produced by the wet phosphoric acid process, and its particle size is 5 to 20 μm. The calcium sulfate in the phosphogypsum will react in the hydration reaction to form needle-shaped calcium sulfonite, which reduces the porosity of the solid waste-based mine filling material and forms a dense skeleton structure, thereby improving its mechanical properties and structural stability. Preferably, in this embodiment, the content of calcium sulfate dihydrate in the phosphogypsum is ≥75wt%, so as to further optimize the mechanical properties of the solid waste-based mine filling material, and to reduce the content of impurities to a certain extent, and reduce the adverse effects of acidic substances in the phosphogypsum on the fluidity of the solid waste-based mine filling material. Exemplarily, the amount of phosphogypsum is 6%, 8%, 10%, 12% or 14%, but is not limited thereto.

[0064] Among them, soda ash can be used as an alkaline activator to promote the progress of the hydration reaction, and it can also partially neutralize the acidic substances in the phosphogypsum and optimize the workability of the solid waste-based mine filling material. Exemplarily, the amount of soda ash is 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5% or 9%, but is not limited thereto.

[0065] Among them, cement can bind the components in the solid waste-based mine filling material. Specifically, the cement can be silicate cement or sulphoaluminate cement, but not limited thereto, preferably silicate cement. The strength grade of cement is 42.5 or 52.5, but not limited thereto. Specifically, the amount of cement is 5 to 20 parts, exemplarily 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts or 19 parts, but not limited thereto. Preferably, it is 5 to 15 parts.

[0066] The foaming agent may be sodium dodecyl sulfate and / or sodium fatty alcohol polyoxyethylene ether sulfate, but is not limited thereto. When used, the foaming agent may be diluted first, and then compressed air may be introduced to form foam. Exemplarily, the amount of the foaming agent is 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%,

[0067] Among them, tailings are wastes generated during mining. Depending on the type of mine minerals, the specific chemical composition and particle size of the tailings are different. In one embodiment, the average particle size of the tailings is 0.5 to 5 mm. Furthermore, the particle size of the tailings meets the following relationship:

[0068] D20*D20 / D80*D20=1.2~2;

[0069] D80 / D20=6-10;

[0070] Among them, D20 is the aperture of the sieve corresponding to 20wt% of the sieve weight, and D80 is the aperture of the sieve corresponding to 80wt% of the sieve weight. The tailings with the above particle size ratio can form a good filling, reduce pores, and improve the mechanical properties of solid waste-based mine filling materials.

[0071] Accordingly, the present invention also discloses a method for preparing a solid waste-based mine filling material, which comprises the following steps:

[0072] (1) preparing modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement and water to prepare a slurry with a water content of 30 to 40 wt %;

[0073] (2) Adding water to a foaming agent to foam to obtain foam, and mixing the foam with the slurry to obtain the product.

[0074] Correspondingly, the present invention also discloses a method for using the above-mentioned solid waste-based mine filling material, which comprises: preparing the solid waste-based mine filling material, pumping it to the goaf for filling, and solidifying it.

[0075] The present invention is described below with specific embodiments:

[0076] Example 1

[0077] This embodiment provides a solid waste-based mine filling material, and its formula is as follows:

[0078] Tailings 20%, S95 slag 30%, modified fly ash 20%, phosphogypsum 10%, soda ash 10%, PO42.5 cement 5%, foaming agent 5%;

[0079] The average particle size of the tailings is 0.5 mm, and D20*D20 / D80*D20=1.54, D80 / D20=8.55, wherein D20 is the aperture of the sieve corresponding to 20 wt% of the sieved weight, and D80 is the aperture of the sieve corresponding to 80 wt% of the sieved weight. The content of calcium sulfate dihydrate in phosphogypsum is 87 wt%. The foaming agent is a mixture of sodium dodecyl sulfate and sodium fatty alcohol polyoxyethylene ether sulfate, and the weight ratio of the two is 1:1.

[0080] The modified fly ash is made from the following raw materials in parts by weight:

[0081] 90 parts of F-type fly ash, 3 parts of alkali (NaOH), 10 parts of PVA, and 6 parts of cellulose. The degree of polymerization of PVA is 1000, and the average particle size of cellulose is 25 μm.

[0082] Wherein, the preparation method of modified fly ash is:

[0083] (1) Take Class F fly ash.

[0084] (2) mixing fly ash with water to obtain a slurry with a concentration of 30 wt%, stirring the mixture thoroughly, standing the mixture for stratification, and removing floating beads on the surface;

[0085] (3) flotation of the first slurry using diesel as a collector and octanol as a foaming agent, filtering and drying the first slurry after flotation to obtain a second intermediate product;

[0086] The weight ratio of diesel to fly ash is 0.8:1000, the weight ratio of octanol to fly ash is 0.6:1000, the flotation time is 4 min, and the aeration volume is 0.35 m 3 / (m 2 ·min).

[0087] (4) treating the second intermediate product with a 30 g / L NaOH aqueous solution at 80° C. for 0.4 h to obtain a first intermediate product; wherein the ratio of the second intermediate product to the NaOH aqueous solution is 90 g:100 mL;

[0088] (5) The first intermediate product is mixed with PVA, cellulose and water to prepare a slurry with a solid content of 10 wt%, reacted at 100° C. for 20 min, and then dried at 65° C. to obtain modified fly ash.

[0089] The preparation method of the solid waste-based mine filling material in this embodiment includes:

[0090] (1) preparing modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement, and water to prepare a slurry with a water content of 35 wt %;

[0091] (2) Add water to a foaming agent to foam to obtain foam (with an apparent density of 50 g / L), and mix the foam with the slurry to obtain the foam.

[0092] Example 2

[0093] This embodiment provides a solid waste-based mine filling material, and its formula is as follows:

[0094] Tailings 20%, S95 slag 25%, modified fly ash 15%, phosphogypsum 15%, soda ash 7%, PO42.5 cement 10%, foaming agent 8%;

[0095] The average particle size of the tailings is 0.5 mm, and D20*D20 / D80*D20=1.72, D80 / D20=9.75, wherein D20 is the aperture of the sieve corresponding to 20 wt% of the sieved weight, and D80 is the aperture of the sieve corresponding to 80 wt% of the sieved weight. The content of calcium sulfate dihydrate in phosphogypsum is 85 wt%. The foaming agent is sodium sulfate of fatty alcohol polyoxyethylene ether.

[0096] The modified fly ash is made from the following raw materials in parts by weight:

[0097] 80 parts of F-type fly ash, 4 parts of alkali (NaOH), 8 parts of PVA, and 5 parts of cellulose. The polymerization degree of PVA is 1000, and the average particle size of cellulose is 20 μm.

[0098] Wherein, the preparation method of modified fly ash is:

[0099] (1) Take Class F fly ash.

[0100] (2) mixing fly ash with water to obtain a slurry with a concentration of 25 wt%, stirring the mixture thoroughly, standing the mixture for stratification, and removing floating beads on the surface;

[0101] (3) flotation of the first slurry using diesel as a collector and octanol as a foaming agent, filtering and drying the first slurry after flotation to obtain a second intermediate product;

[0102] The weight ratio of diesel to fly ash is 1.2:1000, the weight ratio of octanol to fly ash is 0.8:1000, the flotation time is 5 min, and the aeration volume is 0.4 m 3 / (m 2 ·min).

[0103] (4) treating the second intermediate product with a 40 g / L NaOH aqueous solution at 80° C. for 0.5 h to obtain a first intermediate product; wherein the ratio of the second intermediate product to the NaOH aqueous solution is 80 g:100 mL;

[0104] (5) The first intermediate product is mixed with PVA, cellulose and water to prepare a slurry with a solid content of 10 wt%, reacted at 90° C. for 20 min, and then dried at 70° C. to obtain modified fly ash.

[0105] The preparation method of the solid waste-based mine filling material in this embodiment includes:

[0106] (1) preparing modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement, and water to prepare a slurry with a water content of 38 wt %;

[0107] (2) Add water to a foaming agent to foam to obtain foam (with an apparent density of 50 g / L), and mix the foam with the slurry to obtain the foam.

[0108] Example 3

[0109] This embodiment provides a solid waste-based mine filling material, and its formula is as follows:

[0110] Tailings 30%, S95 slag 20%, modified fly ash 15%, phosphogypsum 15%, soda ash 10%, PO42.5 cement 5%, foaming agent 5%;

[0111] The average particle size of the tailings is 0.8 mm, and D20*D20 / D80*D20=1.45, D80 / D20=7.58, wherein D20 is the aperture of the sieve corresponding to 20 wt% of the sieved weight, and D80 is the aperture of the sieve corresponding to 80 wt% of the sieved weight. The content of calcium sulfate dihydrate in phosphogypsum is 83.5 wt%. The foaming agent is sodium sulfate of fatty alcohol polyoxyethylene ether.

[0112] The modified fly ash is made from the following raw materials in parts by weight:

[0113] 80 parts of F-type fly ash, 4 parts of alkali (NaOH), 8 parts of PVA, and 5 parts of cellulose. The polymerization degree of PVA is 1000, and the average particle size of cellulose is 20 μm.

[0114] Wherein, the preparation method of modified fly ash is:

[0115] (1) Take Class F fly ash.

[0116] (2) mixing fly ash with water to obtain a slurry with a concentration of 25 wt%, stirring the mixture thoroughly, standing the mixture for stratification, and removing floating beads on the surface;

[0117] (3) flotation of the first slurry using diesel as a collector and octanol as a foaming agent, filtering and drying the first slurry after flotation to obtain a second intermediate product;

[0118] The weight ratio of diesel to fly ash is 1.2:1000, the weight ratio of octanol to fly ash is 0.8:1000, the flotation time is 5 min, and the aeration volume is 0.4 m 3 / (m 2 ·min).

[0119] (4) treating the second intermediate product with a 40 g / L NaOH aqueous solution at 80° C. for 0.5 h to obtain a first intermediate product; wherein the ratio of the second intermediate product to the NaOH aqueous solution is 80 g:100 mL;

[0120] (5) The first intermediate product is mixed with PVA, cellulose and water to prepare a slurry with a solid content of 10 wt%, reacted at 90° C. for 20 min, and then dried at 70° C. to obtain modified fly ash.

[0121] The preparation method of the solid waste-based mine filling material in this embodiment includes:

[0122] (1) preparing modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement, and water to prepare a slurry with a water content of 38 wt %;

[0123] (2) Add water to a foaming agent to foam to obtain foam (with an apparent density of 50 g / L), and mix the foam with the slurry to obtain the foam.

[0124] Example 4

[0125] This embodiment provides a solid waste-based mine filling material, and its formula is as follows:

[0126] Tailings 20%, S95 slag 25%, modified fly ash 15%, phosphogypsum 15%, soda ash 10%, PO42.5 cement 5%, foaming agent 10%;

[0127] The average particle size of the tailings is 0.8 mm, and D20*D20 / D80*D20=1.45, D80 / D20=7.58, wherein D20 is the aperture of the sieve corresponding to 20 wt% of the sieved weight, and D80 is the aperture of the sieve corresponding to 80 wt% of the sieved weight. The content of calcium sulfate dihydrate in phosphogypsum is 83.5 wt%. The foaming agent is sodium sulfate of fatty alcohol polyoxyethylene ether.

[0128] The modified fly ash is made from the following raw materials in parts by weight:

[0129] 80 parts of F-type fly ash, 4 parts of alkali (NaOH), 8 parts of PVA, and 5 parts of cellulose. The polymerization degree of PVA is 1000, and the average particle size of cellulose is 20 μm.

[0130] Wherein, the preparation method of modified fly ash is:

[0131] (1) Take Class F fly ash.

[0132] (2) mixing fly ash with water to obtain a slurry with a concentration of 25 wt%, stirring the mixture thoroughly, standing the mixture for stratification, and removing floating beads on the surface;

[0133] (3) flotation of the first slurry using diesel as a collector and octanol as a foaming agent, filtering and drying the first slurry after flotation to obtain a second intermediate product;

[0134] The weight ratio of diesel to fly ash is 1.2:1000, the weight ratio of octanol to fly ash is 0.8:1000, the flotation time is 5 min, and the aeration volume is 0.4 m 3 / (m 2 ·min).

[0135] (4) treating the second intermediate product with a 40 g / L NaOH aqueous solution at 80° C. for 0.5 h to obtain a first intermediate product; wherein the ratio of the second intermediate product to the NaOH aqueous solution is 80 g:100 mL;

[0136] (5) The first intermediate product is mixed with PVA, cellulose and water to prepare a slurry with a solid content of 10 wt%, reacted at 90° C. for 20 min, and then dried at 70° C. to obtain modified fly ash.

[0137] The preparation method of the solid waste-based mine filling material in this embodiment includes:

[0138] (1) preparing modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement, and water to prepare a slurry with a water content of 38 wt %;

[0139] (2) Add water to a foaming agent to foam to obtain foam (with an apparent density of 50 g / L), and mix the foam with the slurry to obtain the foam.

[0140] Comparative Example 1

[0141] This comparative example provides a solid waste-based mine filling material, which is different from Example 1 in that the formula does not include a foaming agent, and the rest is the same as Example 1.

[0142] Comparative Example 2

[0143] This comparative example provides a solid waste-based mine filling material, which differs from Example 1 in that the formula does not include soda ash, and the rest is the same as Example 1.

[0144] Comparative Example 3

[0145] This comparative example provides a solid waste-based mine filling material, which is different from Example 1 in that the fly ash is not modified, and the rest is the same as Example 1.

[0146] The solid waste-based mine filling materials of Examples 1 to 4 and Comparative Examples 1 to 3 were tested, and the specific results are as follows: The density test and compressive strength test were tested in accordance with the "Technical Code for Bubble Mixed Lightweight Soil Filling Engineering" CJJ / T177-2012. The shrinkage test and freeze-thaw cycle test were tested in accordance with the "Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering" JTG3441-2024. Water seepage rate test method: 200 ml of filling material slurry was placed in a measuring cylinder, the cylinder mouth was sealed, and the height of the water column exuded from the upper part of the filling body was tested after standard curing for 3 days. The water seepage rate is divided by the height of the filling body.

[0147]

[0148] It can be seen from the above table that the solid waste-based mine filling material in this embodiment can effectively reduce the water seepage rate, improve the anti-freezing and thawing performance, and at the same time ensure relatively stable mechanical properties.

[0149] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A solid waste-based mine filling material, characterized in that: The composition includes the following weight percentages: Tailings 20-50%, slag 10-30%, modified fly ash 10-30%, phosphogypsum 5-15%, soda ash 5-10%, cement 5-10%, foaming agent 1-10%; Wherein, the surface of the modified fly ash forms PVA, polyacrylate or a copolymer of vinyl acetate and acrylate.

2. The solid waste-based mine filling material according to claim 1, characterized in that: The modified fly ash is made from the following raw materials in parts by weight: 80-100 parts of fly ash, 0.5-5 parts of alkali, 5-15 parts of PVA, and 3-12 parts of cellulose.

3. The solid waste-based mine filling material according to claim 1 or 2, characterized in that: The fly ash is Class F fly ash; The base is selected from one or more of sodium hydroxide, potassium hydroxide and triethanolamine; The polymerization degree of the PVA is 800-1200.

4. The solid waste-based mine filling material according to claim 2 or 3, characterized in that: The preparation method of the modified fly ash is: The fly ash is mixed with alkali solution, reacted at 50-90°C for 0.1-0.5h, and the first intermediate product is obtained after solid-liquid separation and drying; wherein the alkali concentration in the alkali solution is 5-50g / L, and the ratio of the alkali solution to the fly ash is 100mL: (80-100)g; The first intermediate product is mixed with PVA, cellulose and water to prepare a slurry with a solid content of 5 to 15 wt%, reacted at 80 to 120° C. for 10 to 40 minutes, and then dried at 60 to 80° C. to obtain modified fly ash.

5. The solid waste-based mine filling material according to claim 4, characterized in that: The step of mixing fly ash and alkali solution, reacting at 50-90° C. for 0.1-0.5 h, and obtaining the first intermediate product after solid-liquid separation and drying comprises: Sorting the fly ash to remove the floating beads and carbon particles in the fly ash to obtain the second intermediate product; The second intermediate product is treated with an alkali solution having a concentration of 10 to 40 g / L for 0.2 to 0.5 h to obtain an intermediate product.

6. The solid waste-based mine filling material according to claim 5, characterized in that: The step of sorting the fly ash and removing the floating beads and carbon particles in the fly ash to obtain the second intermediate product comprises: Mixing fly ash with water to obtain a first slurry with a concentration of 20 to 40 wt%, and removing floating beads on the surface after standing; The first ore pulp is floated using diesel as a collector and octanol as a foaming agent, and the first ore pulp after flotation is filtered and dried to obtain a second intermediate product; The weight ratio of the diesel to the fly ash is (0.3-1.5):1000, the weight ratio of the 2-octanol to the fly ash is (0.4-1.5):1000, the flotation time is 3-5 minutes, and the aeration volume is 0.1-0.5 m 3 / (m 2 ·min).

7. The solid waste-based mine filling material according to claim 1, characterized in that: The foaming agent is sodium lauryl sulfate and / or sodium fatty alcohol polyoxyethylene ether sulfate; The slag is S95 grade slag powder or S105 grade slag powder; The cement is PO42.5 grade cement or PO52.5 grade cement; The content of calcium sulfate dihydrate in the phosphogypsum is ≥75wt%.

8. The solid waste-based mine filling material according to claim 1, characterized in that: The average particle size of the tailings is 0.5-5 mm, and its particle size conforms to the following relationship: D20*D20 / D80*D20=1.2~2; D80 / D20=6-10; Wherein, D20 is the aperture of the sieve corresponding to 20 wt% of the sieved weight, and D80 is the aperture of the sieve corresponding to 80 wt% of the sieved weight.

9. A method for preparing a solid waste-based mine filling material, used for preparing the solid waste-based mine filling material as claimed in any one of claims 1 to 8, characterized in that: include: Prepare modified fly ash by mixing tailings, slag, modified fly ash, phosphogypsum, soda ash, cement and water to prepare a slurry with a water content of 30-40wt%; The foaming agent is added with water to foam to obtain foam, and the foam is mixed with the slurry to obtain the foam.

10. A method for preparing a solid waste-based mine filling material, for using the solid waste-based mine filling material according to any one of claims 1 to 8, characterized in that: include: Prepare solid waste-based mine filling materials, pump them into the goaf for filling and solidification.